Studies on fungus dregs cultivating Tricholoma lobayense Heim - YAN Jing; ZHOU Zu-fa; YUAN Wei-dong; WANG Wei-ke; LU Na; SONG Ji-ling (浙江大学学报. 农业与生命科学版)
In order to reduce the pollution of fungus dregs and conserve the use of raw materials, formulas containing fungus dregs ranging from 0% to 80% were added to cultivate Tricholoma lobayense Heim, and the growth rate, pollution ratio, biological conversion rate and some important nutritional factors (e.g. reducing sugar, total sugar, crude protein, crude fat and fiber) were monitored and measured. The results indicated that biological conversion rate of formulas 1-4 (containing 10%, 20%, 30% and 40% of fungus dregs respectively) were all above 90% and hence suitable for further application. The reducing sugar, crude protein and ash contents of T. lobayense were increased, and the crude fiber content was decreased with the addition of fungus dregs, however, the total sugar, crude fat and water contents were not affected. Among all the formulas, formula 4 (containing 40% fungus dregs) yielded the highest growth rate of 0.280 cm·d-1 and biological conversion rate of 97.85%, and with zero contamination. In conclusion, fungus dregs can be used in the cultivation of T. lobayense, and can effectively improve its yield and quality.